Implementasi Metode Mimicry – Memorization Untuk Meningkatkan Kemampuan Berbicara Bahasa Arab - Ghofur, M. Abdul; Dasuki, Mohammad; Maghfiroh, Anita Harishotul (AS-SUNNIYYAH, 2024)
Learning Arabic is an interesting learning because it uses a foreign language, namely Arabic by using the mim - mem method to improve the ability to speak Arabic. The application of the mim – mem method plays an active role in learning Arabic because it can help students measure student memory. This study aims to find out how the application of the imitation and memorization method (mimicry and memorization) in learning Arabic and to find out whether using the imitation and memorization method (mimicry and memorization) can improve the Arabic speaking ability of students in grade VII J at MTs AS – Sunniyyah. . Here the researcher uses a qualitative descriptive method with data collection techniques in the form of observation, documentation, and written tests. The results of the study found that the mim – mem method can help students learn Arabic by remembering and memorizing the material that has been studied. Then it can also improve the ability to speak Arabic for class VII J students at MTs AS – Sunniyyah Kencong.